The Flipped Classroom Model and Its Impact on EFL Students' Writing Performance and Critical Thinking Dispositions: A Mixed-Methods Study - Safrul Muluk; Syamsul Bahri; Dase Erwin Juansah; Maskur; Fatayatul Hanani Safrul (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2026)
This mixed-methods study investigated the effects of a flipped classroom model on writing performance and critical thinking dispositions among EFL learners. Seventy-four third-year English language teaching students from a university in Indonesia participated in a 14-week quasi-experimental design, with 38 students in the flipped experimental group and 36 in a traditional control group. Data sources included pre- and post-intervention writing samples scored using IELTS band descriptors, the California Critical Thinking Disposition Inventory (CCTDI), semi-structured interviews, and reflective journals. Quantitative analyses revealed significantly larger gains for the experimental group in both writing (mean increase of 1.47 bands versus 0.53, Cohen's d = 0.99) and overall critical thinking dispositions (mean gain of 31.81 points versus 8.52, Cohen's d = 1.07). Subscale analysis showed the largest effects for Truth-seeking, Analyticity, and Confidence in reasoning, with more modest gains for Systematicity and Inquisitiveness. Four themes emerged from qualitative analysis: the cognitive affordance of pre-class preparation, reconceptualization of writing as thinking, social production of thought through peer interaction, and dispositional shifts as identity work. Findings suggest flipped environments can foster both writing development and critical thinking dispositions, though effects vary considerably across learners. The study contributes to understanding mechanisms underlying flipped learning while highlighting the importance of attending to individual differences and the social dimensions of cognitive development.